Dual-channel event microscopy for ultrafast biological imaging - Ruipeng Guo; Xueli Pan; Qilin Deng; Abrar Ahmed; Qianwan Yang; Joseph Greene; Tongyu Li; Suet Ying Chan; Zhixiong Chen; Guorong Hu; Hui Feng; Lei Tian (Proceedings of the National Academy of Sciences, 2026)
Many fundamental biological processes—spanning immune–tumor interactions, neuronal signaling, and microvascular flow—exhibit fast, multiscale dynamics among diverse cell types within three-dimensional tissue environments. Capturing such activity requires imaging systems that simultaneously achieve high temporal resolution, multicolor capability, and large axial coverage over large fields of view (FOVs). However, existing modalities remain limited by trade-offs among imaging speed, spectral capacity, depth of field (DOF), and spatial resolution. Here, we present Dual-Channel Event Microscopy (DEM), which integrates digital micromirror device–based pulsed illumination, extended-DOF (EDOF) optics, and event-based sensing for ultrafast, dual-channel EDOF imaging across a 2.3 × 1.3 mm 2 FOV with an effective 200 μ m DOF. Using dual-color fluorescent phantoms and microsphere flow assays, DEM achieves accurate spectral separation and reconstruction of rapid motion at kilohertz frame rates. In vivo, DEM enables simultaneous visualization of neutrophils and premalignant tumors in freely swimming zebrafish. In immobilized specimens, it provides robust, sensor-level contrast enhancement near the heart, suppressing diffuse background to reveal fine vascular networks and active blood circulation into and out of the cardiac chambers. DEM further enables quantitative mapping of blood-flow dynamics in the zebrafish tail, resolving arterial–venous differences and capturing heartbeat-driven oscillations that reflect cardiac pumping with high temporal fidelity. By combining ultrafast acquisition, dual-channel capability, large axial coverage, and intrinsic contrast enhancement within a single event-driven architecture, DEM offers a powerful platform for visualizing rapid multicellular interactions and physiological dynamics in living systems.